A wear-resistant and crack-resistant polypropylene plastic
Through the combination of polypropylene powder, solubilizer, toughener, paraffin and stearic acid, the grafting rate of solid phase grafting reaction is improved, and the high production cost and unstable material performance in the existing polypropylene modification methods are solved. The problem is to improve the high mechanical properties and wear resistance of polypropylene plastics.
Patent Information
- Application Number
- CN202410654504.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-24
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-05-24
AI Technical Summary
The existing polypropylene modification methods have problems such as the use of toxic solvents for solution grafting, the difficulty in controlling the melt grafting reaction, and the side reaction of solid phase grafting, resulting in high production costs and unstable material performance.
By using polypropylene powder, solubilizer, toughener, mixture of paraffin and stearic acid, filler, C5-C8 cycloalkanes and initiator, the mechanics of polypropylene are enhanced by increasing the graft rate of solid phase graft reaction. Performance and improve wear resistance through the combination of paraffin and stearic acid.
It improves the mechanical properties and wear resistance of polypropylene plastics, enhances its compatibility with fillers, reduces production costs, and reduces environmental pollution.
Smart Images

Figure BDA0004857466580000071 
Figure BDA0004857466580000072
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials and relates to wear-resistant and crack-resistant polypropylene plastic. Background Art
[0002] Polypropylene, abbreviated as PP, is a polymer formed by the addition polymerization of propylene. Polypropylene can be divided into isotactic polypropylene, syndiotactic polypropylene and atactic polypropylene according to the shape of the molecular chain and the spatial arrangement of the methyl group. The chemical formula is (C3H6)n. It is resistant to corrosion by acids, alkalis, salt solutions and various organic solvents below 80°C, and can decompose under high temperature and oxidation. Polypropylene, as the second largest polyolefin product after polyethylene, is a thermoplastic synthetic resin with excellent performance. It is a colorless, translucent, thermoplastic, lightweight general-purpose plastic with chemical resistance, heat resistance, electrical insulation, high-strength mechanical properties and good high-wear-resistant processing properties. It is widely used in the production of daily household furniture, medical equipment, pipes, containers, packaging materials, etc., and is also used in fiber products such as automobiles, clothing, blankets, etc.
[0003] In order to expand the application scope of polypropylene and improve the comprehensive performance of polypropylene. The methods of polypropylene modification include chemical modification and physical modification. Chemical modification mainly includes: copolymerization, grafting, cross-linking, chlorination, etc.; physical modification is through changing the high-level structure of polypropylene materials, mainly including: mixed modification, filling modification, surface modification, etc. Among them, the grafting methods of chemical modification include solution grafting, melt grafting, radiation grafting, suspension grafting and solid phase grafting. However, these methods have shortcomings. Solution grafting requires the use of toxic solvents, long reaction time, high production cost, and easy to cause environmental pollution; the melt grafting reaction process is difficult to control, the product grafting rate is low, and the material performance is unstable; while solid phase grafting is relatively good, no pollution to the environment, low production cost, short reaction time and other advantages, but the reaction has side reactions that will reduce the grafting rate.
[0004] Patent CN113234241B discloses a method for preparing high-performance polypropylene masterbatch. The preparation method comprises the following steps: melt blending PP, thermoplastic elastomer, basic magnesium sulfate whisker and a series of additives in a twin-screw extruder and extruding and granulating to obtain primary polypropylene masterbatch, and then impregnating and drying the polypropylene masterbatch in a silane coupling agent to obtain high-performance polypropylene masterbatch. The preparation process of the invention is simple, and the impregnation method and the reaction with the silane coupling agent improve the product performance. At present, the raw materials used for silane coupling agents are mostly petrochemical products, so there are still certain defects in environmental protection. Summary of the invention
[0005] The present invention relates to a wear-resistant and crack-resistant polypropylene plastic, and belongs to the technical field of polymer materials. The present invention discloses a wear-resistant and crack-resistant polypropylene plastic, which comprises the following raw materials in parts by weight: 100-120 parts of polypropylene powder, 5-10 parts of solubilizer, 5-10 parts of toughening agent, 3-6 parts of a mixture of paraffin and stearic acid, 20-30 parts of filler, 1-3 parts of C5-C8 cycloalkanes, and 1-2 parts of initiator. The present invention improves the mechanical properties of polypropylene plastic by increasing the grafting rate of the solid phase grafting reaction, so that the filler can have good compatibility with polypropylene. Paraffin and stearic acid are compounded to synergistically enhance the wear resistance of polypropylene. Paraffin and stearic acid improve lubrication performance, and the toughening agent enhances flexibility and cooperates with the filler with hardness and rigidity to obtain a wear-resistant and crack-resistant polypropylene material.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A wear-resistant and crack-resistant polypropylene plastic comprises the following raw materials: polypropylene powder, a solubilizer, a toughening agent, a mixture of paraffin and stearic acid, a filler, C5-C8 cycloalkane, and an initiator.
[0008] Furthermore, the polypropylene plastic comprises the following raw materials in parts by weight: 100-120 parts of polypropylene powder, 5-10 parts of solubilizer, 5-10 parts of toughening agent, 3-6 parts of a mixture of paraffin and stearic acid, 20-30 parts of filler, 1-3 parts of C5-C8 cycloalkanes, and 1-2 parts of initiator.
[0009] Furthermore, the preparation method of the wear-resistant and crack-resistant polypropylene plastic comprises the following steps:
[0010] (1) Pretreatment of PP raw materials: PP powder is placed in a Soxhlet extractor for continuous extraction and vacuum drying to obtain pretreated polypropylene;
[0011] (2) adding a solubilizer and C5-C8 cycloalkane to pretreated polypropylene, then adding an initiator, and heating the mixture to obtain HMSPP;
[0012] (3) Add HMSPP, toughening agent, filler, paraffin and stearic acid into a mixer, stir, and extrude into granules.
[0013] Furthermore, the extraction time in step (1) is 5 to 8 hours, and the drying temperature is 50 to 60°C.
[0014] Furthermore, in the step (2), the initiator is benzoyl peroxide, the heating temperature is 100 to 130° C., and the reaction time is 5 to 20 min.
[0015] Furthermore, in the step (2), the solubilizing agent is maleic anhydride and styrene, the mass ratio of the two is 1:1, the C5-C8 cycloalkane refers to at least one of cyclopentane, cyclohexane, cycloheptane and cyclooctane, and the reaction time of adding the solubilizing agent and the C5-C8 cycloalkane is 3-5 minutes.
[0016] Furthermore, the toughening agent in step (3) is any one of polyolefin elastomer, SBS, and EPDM rubber.
[0017] Furthermore, in step (3), the fillers are silicon powder and talcum powder, and the mass ratio of the two is 2:1.
[0018] Furthermore, in the step (3), the mass ratio of paraffin wax to stearic acid is 1:1, and the stirring time is 10 to 15 minutes.
[0019] Beneficial effects of the present invention:
[0020] (1) PP will undergo a grafting reaction with maleic anhydride (MAH) and styrene (St) under the action of benzoyl peroxide (BPO). First, BPO decomposes to produce free radicals, which capture hydrogen on the PP macromolecular chain and generate tertiary carbon free radicals on the PP macromolecular chain. The PP macromolecular chain directly undergoes a grafting reaction with the monomers MAH and St to form a stable macromolecular free radical. However, the PP macromolecular chain itself undergoes β-bond scission degradation to generate two by-products, a PP molecular chain with a double bond at the chain end and a secondary carbon free radical at the chain end. The present invention introduces C5-C8 cycloalkanes to react with the by-product chain end double bond PP molecular chain. Due to the steric hindrance of the chain end double bond PP molecular chain, the C5-C8 cycloalkanes are connected to the α carbon to regenerate the PP macromolecular chain during the reaction. The filler can enhance hardness and rigidity but has poor compatibility with polypropylene, so polar groups are introduced through the monomers MAH and St to make the filler compatible with polypropylene. Therefore, increasing the grafting rate of the solid phase grafting reaction can make the filler have good compatibility with polypropylene, thereby improving the mechanical properties of polypropylene plastics.
[0021] (2) Lubricants can change the lubrication properties of polypropylene and reduce friction to achieve wear resistance. Paraffin wax has an internal lubricating effect and is compatible with polypropylene. By reducing the cohesive energy between molecules inside polypropylene, it weakens the mutual friction between molecules and improves fluidity. Sodium stearate has an external lubricating effect. Lubricant molecules are formed on the surface and have low molecular cohesive energy, which can reduce the friction between polypropylene and other surfaces. Paraffin wax and sodium stearate are compounded to have both internal and external lubricating properties, which has a synergistic effect and improves the wear resistance of polypropylene. DETAILED DESCRIPTION
[0022] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with embodiments.
[0023] Example 1
[0024] A wear-resistant and crack-resistant polypropylene plastic comprises the following raw materials in parts by weight: 100 parts of polypropylene powder, 6 parts in total of maleic anhydride and styrene, 5 parts of polyolefin elastomer, 4 parts of a mixture of paraffin and stearic acid, 21 parts in total of silicon powder and talcum powder, 1 part of cyclohexane, and 1 part of benzoyl peroxide.
[0025] The preparation method of the wear-resistant and crack-resistant polypropylene plastic comprises the following steps:
[0026] (1) PP raw material pretreatment: 100 parts by weight of PP powder was placed in a Soxhlet extractor for continuous extraction for 5 h and then vacuum dried at 50°C;
[0027] (2) Weigh 1 part by weight of benzoyl peroxide and heat it to 100° C., add the pretreated PP powder and react for 5 minutes, then add 3 parts by weight of maleic anhydride and styrene and 1 part by weight of cyclohexane and react for 3 minutes to obtain HMSPP;
[0028] (3) HMSPP, 5 parts by weight of polyolefin elastomer, 14 parts by weight of silicon powder, 7 parts by weight of talc, 2 parts by weight of paraffin wax and stearic acid were added to a mixer and stirred for 10 minutes, followed by extrusion and granulation.
[0029] Example 2
[0030] A wear-resistant and crack-resistant polypropylene plastic comprises the following raw materials in parts by weight: 110 parts of polypropylene powder, 8 parts in total of maleic anhydride and styrene, 8 parts of polyolefin elastomer, 6 parts of a mixture of paraffin and stearic acid, 27 parts in total of silicon powder and talc, 2 parts of cyclohexane, and 2 parts of benzoyl peroxide.
[0031] Furthermore, the preparation method of the wear-resistant and crack-resistant polypropylene plastic comprises the following steps:
[0032] (1) PP raw material pretreatment: 110 parts by weight of PP powder was placed in a Soxhlet extractor for continuous extraction for 6.5 h and then vacuum dried at 55°C;
[0033] (2) Weigh 2 parts by weight of benzoyl peroxide and heat it to 115° C., add the pretreated PP powder and react for 12 minutes, then add 4 parts by weight of maleic anhydride and styrene and 2 parts by weight of cyclohexane and react for 4 minutes to obtain HMSPP;
[0034] (3) HMSPP, 8 parts by weight of polyolefin elastomer, 18 parts by weight of silicon powder, 9 parts by weight of talc, 3 parts by weight of paraffin wax and stearic acid were added to a mixer and stirred for 13 minutes, followed by extrusion and granulation.
[0035] Example 3
[0036] A wear-resistant and crack-resistant polypropylene plastic comprises the following raw materials in parts by weight: 120 parts of polypropylene powder, 10 parts in total of maleic anhydride and styrene, 10 parts of polyolefin elastomer, 6 parts of a mixture of paraffin and stearic acid, 30 parts in total of silicon powder and talcum powder, 3 parts of cyclohexane, and 2 parts of benzoyl peroxide.
[0037] Furthermore, the preparation method of the wear-resistant and crack-resistant polypropylene plastic comprises the following steps:
[0038] (1) PP raw material pretreatment: 120 parts by weight of PP powder was placed in a Soxhlet extractor for continuous extraction for 8 h and then vacuum dried at 60°C;
[0039] (2) Weigh 2 parts by weight of benzoyl peroxide and heat it to 130° C., add the pretreated PP powder and react for 20 minutes, then add 5 parts by weight of maleic anhydride and styrene and 3 parts by weight of cyclohexane and react for 5 minutes to obtain HMSPP;
[0040] (3) HMSPP, 10 parts by weight of polyolefin elastomer, 20 parts by weight of silicon powder, 10 parts by weight of talc, 3 parts by weight of paraffin wax and stearic acid were added to a mixer and stirred for 15 minutes, followed by extrusion and granulation.
[0041] Comparative Example 1
[0042] On the basis of Example 2, a wear-resistant and crack-resistant polypropylene plastic is provided, which comprises the following raw materials in parts by weight: 110 parts of polypropylene powder, 8 parts in total of maleic anhydride and styrene, 8 parts of polyolefin elastomer, 6 parts of a mixture of paraffin and stearic acid, 27 parts in total of silicon powder and talc, and 2 parts of benzoyl peroxide.
[0043] Furthermore, the preparation method of the wear-resistant and crack-resistant polypropylene plastic comprises the following steps:
[0044] (1) PP raw material pretreatment: 110 parts by weight of PP powder was placed in a Soxhlet extractor for continuous extraction for 6.5 h and then vacuum dried at 55°C;
[0045] (2) Weigh 2 parts by weight of benzoyl peroxide and heat it to 115° C., add the pretreated PP powder and react for 12 minutes, then add 4 parts by weight of maleic anhydride and styrene and react for 4 minutes to obtain HMSPP;
[0046] (3) HMSPP, 8 parts by weight of polyolefin elastomer, 18 parts by weight of silicon powder, 9 parts by weight of talc, 3 parts by weight of paraffin wax and stearic acid were added to a mixer and stirred for 13 minutes, followed by extrusion and granulation.
[0047] Comparative Example 2
[0048] On the basis of Example 2, during the composition and preparation of the polypropylene plastic raw material, stearic acid was replaced by an equal weight portion of paraffin.
[0049] Comparative Example 3
[0050] On the basis of Example 2, in the composition and preparation process of the polypropylene plastic raw material, paraffin is replaced by an equal weight portion of stearic acid.
[0051] 1. Determination of HMSPP grafting ratio (GP)
[0052] After the PP powder is dried in the experimental step (1), the PP powders in Examples 1 to 3 and Comparative Example 1 are weighed and recorded as M1. After the reaction in the experimental step (2), the HMSPP in Examples 1 to 3 and Comparative Example 1 is weighed and recorded as M2. The grafting ratio (GP) and grafting efficiency (GE) of polypropylene with MAH and St are calculated as follows:
[0053]
[0054] M1—the quality of PP before modification;
[0055] M2—the quality of modified PP;
[0056]
[0057] M3—mass and weight of grafted monomer;
[0058] The grafting ratio (GP) and grafting efficiency (GE) of polypropylene with MAH and St in Examples 1 to 3 and Comparative Example 1 are shown in Table 1.
[0059] Table 1 Grafting rate (GP) and grafting efficiency (GE) of Examples 1 to 3 and Comparative Example 1
[0060] Example 1 Example 2 Example 3 Comparative Example 1 GP(%) 12.53 13.02 12.45 8.25 GE(%) 91.23 91.32 91.21 87.62
[0061] It can be seen from Table 1 that the grafting rates and grafting efficiencies of Examples 1 to 3 are higher than those of Comparative Example 1, among which the grafting rate of Example 2 is the highest, and the grafting efficiencies of the three Examples are relatively similar. Cyclohexane reacts with the byproduct chain end double bond PP molecular chain to regenerate PP macromolecular chain, which reduces the occurrence of side reactions and thus increases the grafting rate. The increase in the concentration of PP macromolecular chain also increases the grafting efficiency.
[0062] 2. Mechanical properties test of polypropylene plastics
[0063] Prepare the specimens required for the mechanical property test, and put the polypropylene materials prepared in Examples 1 to 3 and Comparative Example 1 into the injection molding machine respectively. The injection molding process parameters are: die temperature 225°C, plasticizing temperature 220°C, barrel temperature 215°C, injection pressure 60 bar, and cooling time 10s. Then press the sheet into a sheet of 100mm×100mm×1mm. The molding process parameters are: the upper and lower plate temperatures are both 190°C, and the molding pressure is 10MPa.
[0064] Tensile properties: The tensile properties test was carried out on an INSTRON material mechanics testing machine according to GB / T1040-2006, with a tensile rate of 50 mm / min and a test temperature of room temperature. Seven specimens were taken from each group for testing and the average value was taken as the final result.
[0065] Bending performance: The bending test was carried out on an INSTRON material mechanics testing machine according to GB / T9341-2008. The test rate was 2 mm / min and the test temperature was room temperature. Seven specimens were taken from each group for testing and the average value was taken as the final result.
[0066] Impact performance: The notched impact strength of the sample is tested on a cantilever beam impact tester according to GB / T1842-2008. Specific method: The injection molded sample is processed into a V-shaped notch on a notch sample making machine, and the arc radius of the notch bottom is 0.25mm. The sample is placed at room temperature for 24 hours before testing. Seven samples are taken from each group for testing and the average value is taken as the final result.
[0067] The test results of tensile strength, flexural strength and impact strength of the polypropylene plastics prepared in Examples 1 to 3 and Comparative Example 1 are shown in Table 2.
[0068] Table 2 Mechanical properties test of polypropylene in Examples 1 to 3 and Comparative Example 1
[0069] Tensile strength / MPa Bending strength / MPa <![CDATA[Impact strength / (kJ·m 2 )]]> Example 1 35.12 30.25 12.45 Example 2 35.21 31.46 13.12 Example 3 35.14 30.56 12.74 Comparative Example 1 26.81 24.37 5.13
[0070] It can be seen from Table 2 that the tensile strength, bending strength and impact strength of Examples 1 to 3 are greater than those of Comparative Example 1. The filler can enhance hardness and rigidity and cooperate with the toughening agent. The addition of the solubilizer enables the filler to have good compatibility with polypropylene, thereby improving the mechanical properties of the polypropylene plastic.
[0071] 3. Wear resistance test
[0072] Test materials: polypropylene materials prepared in Examples 1 to 3 and Comparative Examples 2 to 3.
[0073] Test method: Press the material into a 3mm thin slice, weigh the slice to an accuracy of 0.0001g; fix the slice on the wear tester, and perform a certain number of scrapings under the same conditions; remove the slice and weigh it, and the wear mass can be used as a parameter to evaluate the wear resistance of the material (the smaller the wear mass, the better the wear resistance of the material). Five samples were tested in sequence, and the results are shown in Table 3.
[0074] Table 3 Wear resistance test results
[0075] Group Wear mass / g Example 1 0.8256 Example 2 0.8631 Example 3 0.8463 Comparative Example 2 1.3524 Comparative Example 3 1.2889
[0076] From the data in Table 3, it can be seen that the wear weight of Examples 1 to 3 is less than that of Comparative Examples 2 to 3. The paraffin wax and sodium stearate are compounded to have both internal and external lubrication properties, play a synergistic role, reduce friction, and thus improve the wear resistance of polypropylene.
[0077] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A wear-resistant and crack-resistant polypropylene plastic, characterized in that: The polypropylene plastic comprises the following raw materials in parts by weight: 100-120 parts of polypropylene powder, 5-10 parts of solubilizer, 5-10 parts of toughening agent, 3-6 parts of a mixture of paraffin and stearic acid, 20-30 parts of filler, 1-3 parts of C5-C8 cycloalkane, and 1-2 parts of initiator; The preparation method of the wear-resistant and crack-resistant polypropylene plastic comprises the following steps: (1) Pretreatment of polypropylene raw materials: placing polypropylene powder in a Soxhlet extractor for continuous extraction and vacuum drying to obtain pretreated polypropylene; (2) adding a solubilizer and C5-C8 cycloalkane to pretreated polypropylene, then adding an initiator, and heating the mixture to obtain HMSPP; (3) adding a mixture of HMSPP, toughening agent, filler, paraffin and stearic acid into a mixer, stirring, and extruding and granulating; In the step (2), the solubilizing agent is maleic anhydride and styrene, the mass ratio of the two is 1:1, the C5-C8 cycloalkane is at least one of cyclopentane, cyclohexane, cycloheptane and cyclooctane, and the time for adding the solubilizing agent and the C5-C8 cycloalkane to react is 3-5 minutes; In the step (3), the fillers are silicon powder and talcum powder, and the mass ratio of the two is 2:1; In the step (3), the mass ratio of paraffin wax to stearic acid is 1:
1.
2. The wear-resistant and crack-resistant polypropylene plastic according to claim 1, characterized in that: The extraction time in step (1) is 5-8 hours, and the drying temperature is 50-60°C.
3. The wear-resistant and crack-resistant polypropylene plastic according to claim 1, characterized in that: In the step (2), the initiator is benzoyl peroxide, the heating temperature is 100-130° C., and the reaction time is 5-20 min.
4. The wear-resistant and crack-resistant polypropylene plastic according to claim 1, characterized in that: The toughening agent in step (3) is any one of polyolefin elastomer, SBS, and EPDM rubber.
5. The wear-resistant and crack-resistant polypropylene plastic according to claim 1, characterized in that: The stirring time in step (3) is 10 to 15 minutes.
Citation Information
Patent Citations
A method for preparing high-performance polypropylene masterbatch
CN113234241B
Functionalized polypropylene composite material as well as preparation method and application thereof
CN115895162A